2008
DOI: 10.5194/acp-8-3107-2008
|View full text |Cite
|
Sign up to set email alerts
|

Long-term solar UV radiation reconstructed by ANN modelling with emphasis on spatial characteristics of input data

Abstract: Abstract. Artificial Neural Networks (ANN) are efficient tools to derive solar UV radiation from measured meteorological parameters such as global radiation, aerosol optical depths and atmospheric column ozone. The ANN model has been tested with different combinations of data from the two sites Potsdam and Lindenberg, and used to reconstruct solar UV radiation at eight European sites by more than 100 years into the past. Special emphasis will be given to the discussion of small-scale characteristics of input d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 14 publications
5
29
0
Order By: Relevance
“…The negative relative changes of irradiance during the 1980s and early 1990s suggest that total ozone, as simulated by the CCMs, had not reached its minimum until early 2000s. These changes in irradiance for the northern middle and high latitudes are generally smaller than ∼5% per decade, and they are in accordance with the changes reported for various locations over Europe from measured or reconstructed irradiance data (e.g., Krzyscin et al, 2004;Lindfors et al, 2007;den Outer et al, 2005;Feister et al, 2008;Rieder et al, 2008;Chubarova, 2008). The magnitude of the calculated changes in erythemal irradiance varies significantly, as a result of the variations in the predicted ozone columns from the CCMs.…”
Section: Methodology and Datasupporting
confidence: 69%
See 1 more Smart Citation
“…The negative relative changes of irradiance during the 1980s and early 1990s suggest that total ozone, as simulated by the CCMs, had not reached its minimum until early 2000s. These changes in irradiance for the northern middle and high latitudes are generally smaller than ∼5% per decade, and they are in accordance with the changes reported for various locations over Europe from measured or reconstructed irradiance data (e.g., Krzyscin et al, 2004;Lindfors et al, 2007;den Outer et al, 2005;Feister et al, 2008;Rieder et al, 2008;Chubarova, 2008). The magnitude of the calculated changes in erythemal irradiance varies significantly, as a result of the variations in the predicted ozone columns from the CCMs.…”
Section: Methodology and Datasupporting
confidence: 69%
“…The variability of surface UV radiation in the past has been extensively investigated using both measured and reconstructed records (e.g., Lindfors et al, 2007;Lindfors and Vuilleumier, 2005;Feister et al, 2008;den Outer et al, 2005;Krzyscin et al, 2004;Rieder et al, 2008;Chubarova, 2008), showing increasing of UV irradiance in response to the observed ozone reductions in the 1980s and 1990s. Recent observations suggest that the concentration of ozone depleting substances in the atmosphere have started to decrease as a result of the measures taken under the Montreal Protocol and its Amendments and Adjustments (WMO, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Even though the lowest values of ozone are during 1993, the relative increase in UVB and erythemally weighted UV doses are small in comparison with the range of inter-annual variation. The separation of the mean residuals is estimated at ∼5% which is similar to that seen in the reconstructed values of Feister et al (2008). However, in an earlier paper Feister and Grewe (1995) note a strong seasonal variation in the ozone reduction at Potsdam (52.37°N, 13.08°E) during 1993, so that these effects on the UV annual mean residuals will be somewhat masked.…”
Section: Uv Trendsmentioning
confidence: 57%
“…The ANNs have been employed in diverse applications and fields such as robotics, pattern recognition, forecasting, medicine, power systems, etc. In atmospheric science the use of ANNs is quite recent, for example, ANNs have been successfully used for estimating solar radiation values (Mohandes et al, 1998;Dorvlo et al, 2002;López et al, 2005;Feister and Junk, 2006;Junk et al, 2007;Feister et al, 2008;Paoli et al, 2009;Linares-Rodríguez et al, 2011 or cloud properties (González et al, 2002;Cerdeña et al, 2006). However, their use for AOD estimations is quite recent and limited to short periods.…”
Section: Introductionmentioning
confidence: 99%